2019
DOI: 10.1055/a-1026-6190
|View full text |Cite
|
Sign up to set email alerts
|

„Da muss sich jemand anders kümmern“ – Die medizinische Versorgung von Asylsuchenden als Herausforderung für eine bio-psycho-soziale Medizin

Abstract: ZUSAMMENFASSUNG Ziel der Studie Die Medizin wird verschiedentlich dafür kritisiert, die biologischen Facetten von Gesundheit und Krankheit gegenüber gesellschaftlichen Einflüssen zu privilegieren. Gegen diesen Vorwurf hat sich in den letzten Jahrzehnten ein medizintheoretischer Ansatz etabliert, der ein bio-psycho-soziales Krankheitskonzept vertritt. Dieser Artikel nutzt ethnografische Perspektiven auf die medizinische Versorgung von Asylsuchenden, um zu untersuchen, inwiefern die Prinzipien der bio-psycho-soz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
0
5
0
11
Order By: Relevance
“…Previous studies have shown a high unmet need of treatment of such conditions and a tendency among mentally ill asylum seekers to report with somatic symptoms [72]. Another explanation might lie in the wording of the ASBA, stating in its first paragraph that asylum seekers are entitled to treatment for "acute and painful conditions" [17], which might lead physicians towards treating symptomatically with pain medication, especially when in uncertainty about actual entitlement regulations for their patients [24] or when unwilling or unable to engage for their patients to facilitate equitable treatment and to overcome barriers in access to adequate health care [26,37]. Researchers working on asylum seekers' perceptions of the health care system have described frequent pain killer prescriptions as a symbol for "the lack of interest of and the rejection by the health care system" [73], as they found pain killer prescription being a common trait among failed doctor-patient interactions with asylum seekers [37].…”
Section: Medicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown a high unmet need of treatment of such conditions and a tendency among mentally ill asylum seekers to report with somatic symptoms [72]. Another explanation might lie in the wording of the ASBA, stating in its first paragraph that asylum seekers are entitled to treatment for "acute and painful conditions" [17], which might lead physicians towards treating symptomatically with pain medication, especially when in uncertainty about actual entitlement regulations for their patients [24] or when unwilling or unable to engage for their patients to facilitate equitable treatment and to overcome barriers in access to adequate health care [26,37]. Researchers working on asylum seekers' perceptions of the health care system have described frequent pain killer prescriptions as a symbol for "the lack of interest of and the rejection by the health care system" [73], as they found pain killer prescription being a common trait among failed doctor-patient interactions with asylum seekers [37].…”
Section: Medicationmentioning
confidence: 99%
“…In addition, asylum seekers’ access to health services in Germany is complicated by modulating factors that are shared with other groups of migrants. Studies have identified limited geographic mobility [ 10 , 23 ], language barriers [ 10 , 23 – 25 ], lack of knowledge about the health care system for asylum seekers [ 10 , 24 ], care providers’ lack of knowledge about their patients’ legal situation and realities of life [ 19 , 24 , 26 ] and discrimination and racism [ 24 , 25 , 27 ] as factors hindering asylum seekers in accessing adequate health care.…”
Section: Introductionmentioning
confidence: 99%
“…Anders als in vorangegangenen Studien diskutiert [13][14][15], äußern die Interviewteilnehmer(innen) kaum Misstrauen oder Unbehagen gegenüber den behandelnden Ärzt(inn)en und auch weniger Diskriminierungserfahrungen. Geflüchtete in unserer Studie berichten allerdings von Diskriminierung aufgrund von Sprachkenntnissen, da -wie auch in anderen Studien dokumentiert [28] -wenig Rücksicht auf geringe Deutschkenntnisse genommen wird. Die Übersetzung wird zudem häufig von Laien oder Sozialarbeiter(inne)n übernommen, was die Übersetzungs-und auch die Versorgungsqualität verringern kann [29].…”
Section: Diskussionunclassified
“…Gesetz, und nicht am Stand der Wissenschaft zu orientieren [3,4]. Dies führt zu Versorgungsdefiziten [16][17][18].…”
Section: Diskussionunclassified